2013
DOI: 10.1111/echo.12118
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Simulator‐Based Echocardiography Training of Noncardiologists in Congenital Heart Diseases

Abstract: Our study showed that simulator-based training in echocardiography in CHD could be very effective and may assist with training outside the scope of CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…Emergency medicine skills in the area of pediatrics are rarely offered in the polled STCs in the context of obligatory classes, but would– though not prevalent –in no case be a negligible tool [ 28 ]. Though, as Kessler et al (2013) indicate, there are few studies on whether SBT has an improved clinical impact on pediatric patients, among other things, the exceedingly positive effects of SBT in the area of echocardiography in congenital heart diseases with children is pointed out [ 29 ]. In any case, one has to assume that, even in the context of pediatric emergency medicine, parents and/or relatives as well as residents would welcome comprehensive SBT [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emergency medicine skills in the area of pediatrics are rarely offered in the polled STCs in the context of obligatory classes, but would– though not prevalent –in no case be a negligible tool [ 28 ]. Though, as Kessler et al (2013) indicate, there are few studies on whether SBT has an improved clinical impact on pediatric patients, among other things, the exceedingly positive effects of SBT in the area of echocardiography in congenital heart diseases with children is pointed out [ 29 ]. In any case, one has to assume that, even in the context of pediatric emergency medicine, parents and/or relatives as well as residents would welcome comprehensive SBT [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…showed that anesthesia residents using a TTE simulation program demonstrated superior success rates with regional anesthesia nerve blocks when compared to their peers that did not undergo training with the simulation program. Another study analyzed noncardiology residents in using bedside TTE in evaluating congenital heart disease, almost all of whom had had little to no prior training, and found that undergoing training with a simulator program likely improved their ability to diagnose congenital heart disease . As bedside TTE becomes more commonplace, and advances in technology make it more accessible, clinicians will have another vital diagnostic tool to aid in patient care.…”
Section: Role Of Simulated Ttementioning
confidence: 99%
“…59 Those practitioners who subspecialize in pediatric cardiac anesthesiology may also benefit from somewhat more specific simulation in this area. 60,61 Transducer manipulation may also be taught with the simulator, its feel, weight, and angulation to the skin or esophagus, essential for image optimization. This is all the more important in TEE, where a clumsy or inexperienced trainee has the potential to cause significant harm.…”
Section: Simulation For Spatial Orientation In Echocardiographymentioning
confidence: 99%